The troubled man - Mankell, Henning, 1948-2015 (Mankell, Henning, 1948-2015. Kurt Wallander mystery., 2012)
When Kurt Wallander is called into the case of the disappearance of a retired naval officer, coincidentally his daughter's future father-in-law, he becomes embroiled in a story of Cold War espionage.